2009
DOI: 10.1248/cpb.57.1189
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Cembranoids from the Cultured and Wild-Type Soft Corals Sinularia flexibilis

Abstract: In previous studies a series of novel secondary metabolites, including cembranes, [1][2][3][4][5][6][7][8][9][10][11][12] eunicellin-based compounds, 13) and other metabolites, [14][15][16][17] have been isolated from the soft coral Sinularia flexibilis (Quoy and Gaimard). Some of these were found to exhibit cytotoxic activity against the growth of various cancer cell lines. 1,[3][4][5][6][10][11][12] During the course of our investigation on new natural substances from the cultured and wild-type soft corals S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…This advanced technique has made in-depth pharmacological studies of metabolites of soft corals possible. In our previous research on bioactive metabolites, our group (National Museum of Marine Biology & Aquarium) isolated several cembrane terpenes from cultured soft corals Sinularia f lexibilis, 6 Sinularia gibberosa, 7 Sinularia numerosa, 8 Sarcophyton trocheliophorum, 9 and Lobophytum crassum. 10 Our recent study of the bioactive natural products derived from two cultured soft corals, S. sandensis and S. f lexibilis, resulted in the isolation of five new cembranoids, 4-carbomethoxyl-10-epigyrosanoldie E (1), 7-acetylsinumaximol B (2), diepoxycembrene B (6), dihydromanaarenolide I (8), and isosinulaflexiolide K (9), as well as several known metabolites, 3−5, 7, and 10−16 ( Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This advanced technique has made in-depth pharmacological studies of metabolites of soft corals possible. In our previous research on bioactive metabolites, our group (National Museum of Marine Biology & Aquarium) isolated several cembrane terpenes from cultured soft corals Sinularia f lexibilis, 6 Sinularia gibberosa, 7 Sinularia numerosa, 8 Sarcophyton trocheliophorum, 9 and Lobophytum crassum. 10 Our recent study of the bioactive natural products derived from two cultured soft corals, S. sandensis and S. f lexibilis, resulted in the isolation of five new cembranoids, 4-carbomethoxyl-10-epigyrosanoldie E (1), 7-acetylsinumaximol B (2), diepoxycembrene B (6), dihydromanaarenolide I (8), and isosinulaflexiolide K (9), as well as several known metabolites, 3−5, 7, and 10−16 ( Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have indicated that diterpenes, a main constituent of the genus Sinularia , exhibit various biological activities, such as anti-inflammatory (Chao et al 2011; Cheng et al 2010; Lu et al 2010; Su and Wen 2011), antiviral (Cheng et al 2010), and cytotoxic (Grote et al 2008; Kamel et al 2007; Lo et al 2009; Su et al 2009) effects. As a part of our ongoing investigations on screening active compounds from Vietnamese Sinularia soft corals towards anti-inflammatory effects (Thao et al 2012, 2013a, b), we recently reported the isolation, structure elucidation, and inhibitory effects on lipopolysaccharide-stimulated production of proinflammatory cytokines in bone marrow-derived dendritic cells of 12 diterpenoids [sinumaximol A ( 1 ), sinumaximol B ( 2 ), sinumaximol C ( 3 ), sethukarailin ( 4 ), sinumaximol D ( 5 ), sinumaximol E ( 6 ), sinumaximol F ( 7 ), sinumaximol G ( 8 ), sinumaximol H ( 9 ), (1 S ,2 E ,4 S ,6 E ,8 S ,11 R )-2,6,12(20)-cembratriene-4,8,11-triol ( 10 ), isomandapamate ( 11 ), and sinumaximol I ( 12 )] (Thao et al 2012) and 7 norditerpenoids [scabrolide A ( 13 ), 12-hydroxy-scabrolide A ( 14 ), yonarolide ( 15 ), ineleganolide ( 16 ), 5-epinorcembrene ( 17 ), 13- epi -scabrolide C ( 18 ), and norcembrene 5 ( 19 )] (Thao et al 2013a) from Sinularia maxima (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 64 was cytotoxic on mouse neuroblastoma cells (N18-T62) at low concentrations (0.16 μM), whereas significantly reduced cell proliferation of human tumoral cells (DU-145 and MCF-7) in a dose-depending manner [30]. Two new cembrane-type diterpenoids have been isolated from the 2-propanol extract of the sea pen Gyrophyllum sibogae collected in South Africa: 7,8-dihydroflabellatene A (66) and 7,8-dihydroflabellatene B (67). Compound 66 showed the activity against all of the lines tested.…”
Section: Isopropyl Cembranesmentioning
confidence: 99%